2002
DOI: 10.1067/mva.2002.119042
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages are associated with lipid-rich carotid artery plaques, echolucency on B-mode imaging, and elevated plasma lipid levels

Abstract: Increased macrophage density in carotid atherosclerotic plaques was associated with lipid content, plaque echolucency, and increased plasma and low-density lipoprotein cholesterol levels. Furthermore, use of aspirin was associated with reduced macrophage density in carotid artery plaques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
69
0
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(80 citation statements)
references
References 34 publications
8
69
0
3
Order By: Relevance
“…Histological evidence suggests that homogeneous echogenicity is found in collagenrich, fibrous plaques, and heterogeneous echogenicity is found in lipid-rich or hemorrhagic plaques, 14,15 usually associated with an increased number of macrophages. 19 The value of such classification is supported by its prognostic significance, because echolucent (complex) carotid plaques were found to be associated not only with a 3-fold-higher risk of ipsilateral ischemic stroke but also with a 2-fold-higher risk of cardiac ischemic events than echorich (simple) carotid plaques. 20 Thus, such "complex" plaques appear to be potentially "unstable."…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Histological evidence suggests that homogeneous echogenicity is found in collagenrich, fibrous plaques, and heterogeneous echogenicity is found in lipid-rich or hemorrhagic plaques, 14,15 usually associated with an increased number of macrophages. 19 The value of such classification is supported by its prognostic significance, because echolucent (complex) carotid plaques were found to be associated not only with a 3-fold-higher risk of ipsilateral ischemic stroke but also with a 2-fold-higher risk of cardiac ischemic events than echorich (simple) carotid plaques. 20 Thus, such "complex" plaques appear to be potentially "unstable."…”
Section: Discussionmentioning
confidence: 64%
“…There was no significant difference in the prevalence of carotid plaques in patients with unstable or stable angina (77.6% versus 64.0%, respectively; Pϭ0. 19). Similarly, there was no difference in the prevalence of carotid artery stenoses between the 2 groups (29.9% versus 20.0%, respectively; Pϭ0.35).…”
Section: Prospective Studymentioning
confidence: 87%
“…Additionally metoprolol treatment decreased a histological vulnerability index, based on percent macrophages and lipids divided by percent of smooth muscle cells and fibers, in abdominal aortic plaques in rabbits [18]. Previous studies on human plaques have shown that echolucent plaques contain more lipids [8] and macrophages [9], while calcium [8,10] and fibrous tissue [8] are more frequently found in echogenic subtypes. These reports are in accordance with the findings of the present study that metoprolol treatment is associated with an increase in plaque echogenicity in humans.…”
Section: Discussionmentioning
confidence: 85%
“…The results of these studies indicate that echolucent plaques are associated with an increased risk for ischemic cerebrovascular events independent of degree of stenosis [6,7]. Echolucent plaques have been shown to contain more lipids [8], macrophages [9], and elastin [10] in comparison to more echogenic lesions.…”
Section: Introductionmentioning
confidence: 90%
“…The association of macrophages and plaque lipid content and hemorrhage has been established 65,66 . In a study of 106 patients who had DU and subsequently underwent endarterectomy with plaque histology analysis, a higher concentration of macrophages in the plaque was related to more echolucent plaques 65 .…”
Section: Plaque Content and Distributionmentioning
confidence: 99%